Game changers for irrigated agriculture—do the right incentives exist? - Bird, Jeremy (2014)
Game changers to achieve sustainable intensification of agriculture are possible in the irrigation sector and they focus mainly on getting more with less. There is, however, still a long way to go to replicate, adapt and develop approaches to take such ideas to scale and increase productivity within existing agricultural water management contexts. Recognizing this, the CGIAR Research Program on Water, Land and Ecosystems (WLE) seeks to achieve sustainable intensification through productive and efficient use of resources, restoring the productive capacity of degraded agricultural landscapes and reducing risk and uncertainty through the sustainable management of land and water resources. WLE research has contributed to reductions in fertilizer use through substitution with reused organic waste products, improved groundwater governance in India and changing the policy framework for smallholder farmers in Africa to improve their access to simple water management technologies. Achieving more widespread adoption of these kinds of practices requires evidence which can increase our understanding of the constraints and effectiveness of different options; an openness to explore new and sometimes counter-intuitive ideas; working across institutional boundaries; consideration of the rainfed to irrigation continuum; and a commitment to provide the necessary policy framework, capacity and resources to support incentives for change.